Bacon and the mind art, neuroscience and psychology - Bucklow, Christopher 1957-; Jaron, Steven; Leader, Darian; Onians, John 1942-; Zeki, Semir (Thames & Hudson, 2019)
The Estate of Francis Bacon published the five-volume catalogue raisonne of Bacon's paintings in 2016. In line with its intention to facilitate original research and writing on Bacon, The Estate will launch a series of books, 'Francis Bacon Studies', in 2019. Three titles are currently in production, the first of which, 'Bacon and the Mind', will be published in May 2019. The five authors of Bacon and the Mind are all prominent scholars in their various disciplines. Their original perspectives on Bacon illuminate his art and his motivations, and they open up new ways of understanding his paintings
Keywords: Bacon, Francis -- 1909-1992; Bacon, Francis / 1909-1992 / Criticism and interpretation; Bacon, Francis / 1909-1992; Criticism, interpretation, etc; Aufsatzsammlung